Guidelines for the Development and Management of Performance Assessments - Edward D. Roeber (Practical Assessment, Research, and Evaluation, 1996)
Accessed 73,595 times on https://pareonline.net from November 13, 1999 to December 31, 2019. For downloads from January 1, 2020 forward, please click on the PlumX Metrics link to the right.
Keywords: Achievement Tests; Educational Assessment; *Educational Policy; Elementary Secondary Education; Field Tests; *Performance Based Assessment; *Scoring; *Test Construction; Test Use; *Testing Problems; Training